Background paper on the needs of migrant, refugee and asylum seeker patients around the globe. Issue 3 (2nd July 2016) - Schouler-Ocak, Meryam; Wintrob, Ronald; Moussaoui, Driss; Villasenor Bayardo, Sergio J.; Zhao, Xu-Dong; Kastrup, Marianne C.
ABSTRACT: This background paper aims to better understand and classify the needs of migrant, refugee and asylum seeker patients worldwide, and provides background information on the subject.